1990
DOI: 10.1128/jcm.28.5.956-961.1990
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of bacterial pathogens associated with infectious diarrhea in Djibouti

Abstract: During a survey examining the causes of diarrhea in the East African country of Djibouti, 140 bacterial pathogens were recovered from 209 diarrheal and 100 control stools. The following pathogens were isolated at comparable frequencies from both diarrheal and control stools: enteroadherent Escherichia coli (EAEC) (10.6 versus 13%), enterotoxigenic E. coli (ETEC) (11 versus 10%), enteropathogenic E. coli (EPEC) (7.7 versus 12%), Salmonella spp. (2.9 versus 3%), and Campylobacterjejuni-C. coli (3.3 versus 5%). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
5
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 14 publications
2
18
5
1
Order By: Relevance
“…However, the current difficult economic situation poses an obstacle. The etiological agents associated with diarrhea were not remarkably different from those of other African countries (1,(9)(10)(11)(12)15). Cases of endemic diarrhea in the study population were not found.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, the current difficult economic situation poses an obstacle. The etiological agents associated with diarrhea were not remarkably different from those of other African countries (1,(9)(10)(11)(12)15). Cases of endemic diarrhea in the study population were not found.…”
Section: Discussionmentioning
confidence: 73%
“…Epidemiological studies on diarrhea have been reported from several African countries including South Africa (6,8,14), Djibouti (9), Gambia (12), Somalia (1), Ethiopia (15), Guinea-Bissau (10), and Nigeria (11). However, there is no published information on Kenya.…”
mentioning
confidence: 99%
“…Although EAEC have been associated with diarrhea in children in Africa, the role of EAEC in diarrhea has been controversial. 9,17,18 In studies from Djibouti and Bangladesh, EAEC were not significantly associated with diarrhea. 17,19 However, in children between six months and 12 years of age, EAEC were significantly associated with diarrhea.…”
Section: Discussionmentioning
confidence: 96%
“…9,17,18 In studies from Djibouti and Bangladesh, EAEC were not significantly associated with diarrhea. 17,19 However, in children between six months and 12 years of age, EAEC were significantly associated with diarrhea. 9,18 In the present study, EAEC were detected in 57 of 150 children with diarrhea.…”
Section: Discussionmentioning
confidence: 96%
“…The emergence of antimicrobial resistance in enteric bacterial pathogens is a major problem associated with the control of diarrhoea. Various authors have reported high rates of resistance to commonly used, inexpensive, oral antimicrobial agents such as ampicillin, tetracycline, and trimethoprim‐sulphamethaxozole ( Mikhail et al . 1990 ).…”
Section: Introductionmentioning
confidence: 99%